Towards a consistent safety format of steel beam-columns: application of the new interaction formulae from ambient temperature to elevated temperatures - Vila Real, P.M.M. (2010)
Two new formulae for the design of beam-columns at room temperature have been proposed into Eurocode 3, prEN 1993-1-1 (2002), and are the result of great efforts made by two working groups that followed different approaches, a French-Belgian team and an Austrian-German one. Under fire conditions the prEN 1993-1-2 (structural fire design) presents formulae, for the design of beam-columns based on the prENV 1993-1-1 (1992). In order to study the possibility of having, in part 1-1 and part 1-2 of the Eurocode 3, the same approach, a numerical research was made using the finite element program SAFIR, developed at the University of Liege for the study of structures subjected to fire.